Risk factors for missed abortion: retrospective analysis of a single institution’s experience - Wei-Zhen Jiang; Xi-Lin Yang; Jian-Ru Luo (Reproductive Biology and Endocrinology, 2022)
Abstract Objective To explore the risk factors including the difference between mean gestational sac diameter and crown-rump length for missed abortion. Methods Hospitalized patients with missed abortion and patients with continuing pregnancy to the second trimester from Chengdu Women's and Children's Central Hospital from June 2018 to June 2021 were retrospectively analyzed. The best cut-off value for age and difference between mean gestational sac diameter and crown-rump length (mGSD-CRL) were obtained by x-tile software. Univariate and multivariate logistic regression analysis were adopted to identify the possible risk factors for missed abortion. Results Age, gravidity, parity, history of cesarean section, history of recurrent abortion (≥ 3 spontaneous abortions), history of ectopic pregnancy and overweight or obesity (BMI > 24 kg/m2) were related to missed abortion in univariate analysis. However, only age (≥ 30 vs < 30 years: OR = 1.683, 95%CI = 1.017–2.785, P = 0.043, power = 54.4%), BMI (> 24 vs ≤ 24 kg/m2: OR = 2.073, 95%CI = 1.056–4.068, P = 0.034, power = 81.3%) and mGSD-CRL (> 20.0vs ≤ 11.7 mm: OR = 2.960, 95% CI = 1.397–6.273, P = 0.005, power = 98.9%; 11.7 < mGSD-CRL ≤ 20.0vs > 20.0 mm: OR = 0.341, 95%CI = 0.172–0.676, P = 0.002, power = 84.8%) were identified as independent risk factors for missed abortion in multivariate analysis. Conclusion Patients with age ≥ 30 years, BMI > 24 kg/m2 or mGSD-CRL > 20 mm had increasing risk for missed abortion, who should be more closely monitored and facilitated with necessary interventions at first trimester or even before conception to reduce the occurrence of missed abortion to have better clinical outcomes.